Single-Fed Broadband CP Bidirectional Antenna with Double-Layer Diagonally Aligned Plates for Universal UHF-RFID Applications - Sitthichai Dentri; Khanet Pookkapund; Bancha Luadang; Prayoot Akkaraekthalin; Chuwong Phongcharoenpanich (International Journal of Antennas and Propagation)
This research proposes a single-fed broadband circularly polarized (CP) bidirectional antenna operable in 840–960 MHz frequency band for readers of universal UHF-RFID applications. The proposed antenna is comprised of upper-layer conductor, lower-layer conductor, and wall patches. The upper-layer conductor consists of two diagonally aligned rectangular copper plates with a feeding gap at the center, and the lower-layer conductor is of two diagonally adjoined rectangular plates. The upper- and lower-layer conductors are adjoined with the wall patches. The diagonal alignment technique of the upper- and lower-layer plates was used to realize circular polarization and improve 3-dB axial ratio (AR) bandwidth. The double layers were deployed to improve impedance bandwidth (|S11| < −10 dB) and achieve bidirectional radiation pattern. The simulated impedance bandwidth and 3-dB AR bandwidth were 772.19–1014.6 MHz (27.13%) and 675–1000 MHz (38.80%), and the corresponding measured results were 759–1011 MHz (28.47%) and 648–1110 MHz (52.55%). The simulated LHCP/RHCP half-power beamwidth (HPBW), 3-dB AR beamwidth, and gain were 56° – 90°/54° – 92°, 60° – 104°, and 4.94 – 5.89 dBic, while the corresponding measured results were 52° – 98°/62° – 97°, 96° – 126°, and 4.28 – 5.72 dBic. As a result, the single-fed broadband CP bidirectional antenna is applicable to universal UHF-RFID readers. Besides, the novelty of this research lies in the use of diagonal alignment of conducting plates to achieve circular polarization and wider AR bandwidth.